Coffee Agro-industry Conceptual Model Using System Dynamics in Lampung Province, Indonesia - Rosiana, Nia; Feryanto, Feryanto; Simorangkir, Nadya Carolina (Department of Agro-industrial Technology, University of Brawijaya, 2024)
AbstractThe consumption trend of coffee downstream products is increasing every year. However, the high variation in the quality of raw materials on the upstream side impacts agroindustrial activities. The limited capacity of processed coffee production indicates that coffee processing activities are not optimal. High competition and individual business activities cause the upstream and downstream linkage of the coffee industry to be limited. The research objective is to analyze the conceptual model of coffee agro-industry development based on the complexity of problems faced by the actors. Primary and secondary data are used as the basis for compiling the conceptual model of the coffee agro-industry using Vensim Software PLE 9.3.5x64. The conceptual sub-models built are farmers, intermediary traders, and processors. Coffee agro-industry is developed by improving the quality and continuity of raw materials, processing capacity, and the actors' skills. Quality and production are connecting variables of the three submodels built. The quality of raw materials produced by farmers will improve the quality of processed coffee. Improving the quality of raw materials is not only from using superior seeds but also from the technical skills of the actors involved. Increased processing capacity can increase the absorption capacity of the coffee agro-industry. Keywords: coffee, dynamic model, intermediary traders, processors, farmers Abstrak Tren konsumsi produk hilir kopi meningkat setiap tahun, tetapi variasi yang tinggi pada kualitas bahan baku di sisi hulu berdampak pada kegiatan agroindustri. Kapasitas produksi olahan kopi yang terbatas mengindikasikan bahwa kegiatan pengolahan kopi belum optimal. Persaingan yang tinggi dan kegiatan usaha yang individual menyebabkan linkage hulu dan hilir industri kopi terbatas. Tujuan penelitian ini adalah menganalisis model konseptual pengembangan agroindustri kopi berdasarkan kompleksitas permasalahan yang dihadapi para pelaku agroindustri kopi. Penelitian dilakukan di Kabupaten Lampung Barat, Provinsi Lampung, Indonesia. Data primer dan sekunder digunakan sebagai dasar penyusunan model konseptual agroindustri kopi dengan menggunakan Software Vensim PLE 9.3.5x64. Submodel konseptual yang dibangun adalah petani, pedagang perantara, dan pengolah. Pengembangan agroindustri kopi dilakukan melalui peningkatan kualitas dan kontinyuitas bahan baku, kapasitas pengolahan, dan skill para pelaku yang terlibat. Kualitas dan produksi menjadi variabel penghubung dari ketiga submodel yang dibangun. Kualitas bahan baku yang dihasilkan petani akan meningkatkan kualitas mutu kopi olahan. Peningkatan kualitas bahan baku dipengaruhi oleh penggunaan bibit unggul dan peningkatan skill teknis dari para pelaku yang terlibat. Peningkatan kapasitas pengolahan dapat meningkatkan daya serap agroindustri kopi.Kata kunci: kopi, model dinamis, pedagang perantara, pengolah, petani